2018
DOI: 10.1371/journal.pone.0202112
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of excision repair cross-complementing group 1 genotypes to triple negative breast cancer risk

Abstract: Compared with other subgroups of breast cancer, triple negative breast cancer (TNBC) is considered to be the one with the greatest invasiveness and metastatic mobility, and the highest recurrence rate. Considering the lack of predictive markers for TNBC, we aimed to examine the contribution of excision repair cross complementing-group 1 (ERCC1) genotypes to TNBC. The rs11615 and rs3212986 of ERCC1 were investigated and evaluated for their associations with susceptibility to breast cancer, especially TNBC, in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…In the present study, the results of the association analysis indicated that the ERCC1rs3212986 (C8092A) polymorphism was not associated with breast cancer risk in the study population ( p > .05). The same result was reported in the Taiwanese population in 2018 (Tsai et al, 2018 ), Chinese in 2013 (Yang et al, 2013 ), and American in 2006 (Shen et al, 2006 ). In contrast, a case–control study (872 cases and 671 controls) conducted by Lee et al in the Korean population indicated that the AA mutant genotype of the polymorphism is associated with a risk of breast cancer (Lee et al, 2005 ).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, the results of the association analysis indicated that the ERCC1rs3212986 (C8092A) polymorphism was not associated with breast cancer risk in the study population ( p > .05). The same result was reported in the Taiwanese population in 2018 (Tsai et al, 2018 ), Chinese in 2013 (Yang et al, 2013 ), and American in 2006 (Shen et al, 2006 ). In contrast, a case–control study (872 cases and 671 controls) conducted by Lee et al in the Korean population indicated that the AA mutant genotype of the polymorphism is associated with a risk of breast cancer (Lee et al, 2005 ).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it is well known that cancer stem cells gain the enhanced DNA repair capacity, rendering them resistant to radiation [ 47 ]. Notably, our findings showed that pre-treatment with MPSE mediated down-regulation of DNA repair proteins such as DNA excision repair protein (ERCC5) [ 48 ], neuroepithelial cell-transforming gene 1 protein (NET1) [ 49 ], BRCA2-interacting transcriptional repressor (EMSY) [ 50 ], and junctional adhesion molecule A (F11R), which enhanced the radiosensitivity of breast cancer cells by reducing the formation of cancer stem cells. These findings are consistent with our earlier results (γH2AX), which revealed that the combination treatment of MPSE with IR enhances the efficacy of IR by increasing IR-induced DNA damage and IR-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was reviewed and approved by the Institutional Review Board of China Medical University Hospital (DMR99-IRB-108). Briefly, a total of 2464 subjects were recruited, including 1,232 female patients diagnosed with breast cancer and exactly the same number of age-matched healthy individuals visiting the China Medical University Hospital, one of the national medical centers in central Taiwan (22)(23)(24). The exclusion criteria for recruiting the healthy controls included any metastatic cancer of any origin, any previous malignancy, and any hereditary or genetic disease.…”
Section: Methodsmentioning
confidence: 99%